Edukasi Isi Piringku sebagai Upaya Pencegahan Stunting - Heni Heryani; Ayu Endang Purwati; Henri Setiawan; Andan Firmansyah; Rosidah Solihah (Yayasan Inspirasi El Burhani, 2023)
Introduction: Stunting if not treated immediately will have a negative impact on the future of the nation. One of the efforts that can be made to prevent stunting is to provide balanced nutrition from an early age in the first 1000 days of life. The contents of my plate is one step to achieve balanced nutrition. One of the efforts to shape eating behavior is to educate pregnant women and cadres about what is on my plate. Objective: The purpose of this community service activity is to provide education about the contents of my plate so that there is an increase in knowledge about balanced nutrition for pregnant women and cadres. Method: Community service activities are carried out in the Village of Aula Pamarican. The method used in this community service activity is lectures using slides and leaflets. The target of this activity is pregnant women and cadres, with a total of 40 people. Community service activities begin with a pretest and end with a posttest to measure the increase in target knowledge. Result: The results of the service show that the average pretest has less knowledge, namely 65%. After education, the average knowledgeable enough is 62.5%. Conclusion: Education The contents of my plate can increase the knowledge of pregnant women and cadres as an effort to prevent stunting.